Systematic Literature Review: The Effectiveness of Technology-Assisted Project-Based English Language Learning - Rochimah, Heni; Japar, Muhammad; Solihatin, Etin (Participatory Educational Research, 2025)
The problem with learning English lies in the need for updated instructional methods. Project-based learning, a contemporary model suited for the 21st century, fosters collaboration to ignite students' enjoyment of learning. The increasing use of technology in learning is establishing a new effectiveness learning model. This research aims to determine the influence of technology-assisted and project-based learning (TPjBL) on English language acquisition, analyze factors that influence the TPjBL on English language learning, and analyze media used in implementing TPjBL in English language learning. The research methods involved a systematic literature review, analyzing 23 (twenty-three) articles selected through the PRISMA process from 2015 to 2023. The data analysis technique utilized a predetermined review protocol containing three main aspects, including bibliography, research details, as well as focus and content of the article. Based on the consequences of the analysis using protocol review, it was found that the positive influence of TPjBL on English learning was 91%, with influencing factors including student conditions, technology features, authentic projects, group communication and collaboration, teacher conditions, as well as the most widely used media of social media and web. These three parties can benefit from the results of this study. Teachers must be able to create good learning plans (project planning, technology selection), preliminary activities and appropriate assessment principles. For schools and governments, curriculum adjustments, technological facilities, such as computers, and the availability of internet access must be reviewed if determining to implement TPjBL in English learning.